Passsenger Ride Comfort and International Roughness Index Specifications in the Slovak Republic - Peter Mucka; George Juraj Stein; Peter Tobolka (Communications - Scientific letters of the University of Zilina, 2019)
New original results are presented on relation between passenger’s whole-body vibration (WBV) and longitudinal road unevenness characterised by the International Roughness Index (IRI) in 100-m segments. Measurements were provided in nine different cars of six vehicle categories operated on about 1860 km of road network. Vibration total value based on the root mean square (RMS) of the frequency-weighted acceleration was used to quantify the ride comfort at seat surface and seat base (i.e. vehicle floor) in three orthogonal axes. The relations between passenger’s acceleration response, comfort reaction levels according to the ISO 2631-1: 1997 and the IRI road unevenness classes, used by the Slovak Road Administration, were estimated. Results indicated higher WBV by ~ 20 % on the motorways than on the 1st and 2nd class roads in the same IRI road class. Using the same IRI road classes for motorways and the 1st and 2nd class roads seems not to be appropriate from the point of view of the whole-body vibrations.